Inoculation of Soil Cyanobacteria Improves Fertility of a Soil Mixed with Copper Tailing Sands - Ortiz-Calderon, C; Pontigo-Gallardo, D (Avestia Publishing, 2019)
Industrial activities such as mining provoke soil degradation which can be restored by applying cyanobacteria as inoculants to promote biocrust development. However, previous to the field applications, there is a need to determine the cyanobacterial suitable species under laboratory conditions. In this investigation, a culture of Trichormus sp. isolated from environmental samples was inoculated on a soil mixed with copper tailing sands. The establishment of the cyanobacteria on the substrate was determined by confocal microscopy, and germination and growth of Polypogon australis, a tailing storage facility (TSF) natural colonizer were determined. In addition, the total nitrogen content (N), phosphorus available (P) and organic matter (OM) content of the inoculated substrates was measured after 30 days. The results showed that the cyanobacterial culture increases the speed but not the cumulative germination of P. australis, and generates an increase of available P, total N and OM of the mixed soil. The improvement in soil fertility and stability of tailing sands supports the use of cyanobacteria to restore degraded or mining polluted soils. © 2019 Avestia Publishing.